Carbon stocks in the Oak and Pine Forests in Salyan District, Nepal - Shrestha, Bishnu Prasad; Devkota, B. P. (Banko Janakari, 2016)
Forests play an important role in absorbing atmospheric carbon dioxide. Broadleaf Forests absorb more carbon as compared to the Pine Forests. Quantification of carbon in any vegetation and soil type is a basic step for evaluating the carbon sequestration potential of an ecosystem. To quantify the vegetation and soil carbon stocks in Oak and Pine Forests, above and below-ground biomass of both forests were estimated using stratified random sampling. Individual trees in the sample plots of both forest types were measured. Above-ground biomass of trees and saplings were estimated by using different models, while the biomass of grass, herb and litter were calculated directly from field measurements. To determine the soil carbon stock, soil samples from three depth levels (0–10 cm, 10–20 cm, and 20–30 cm) of each soil profile were collected for each sample plot laid out in both forest types. Total vegetation carbon stocks in Oak and Pine Forests were 90.37 and 24.82 Mg C ha-1, respectively. Similarly, the soil carbon stocks in the Oak and Pine Forests were 60.82 and 46.12 Mg C ha-1, respectively. Banko Janakari, Vol. 23, No. 2, 2013